Kriminalitas dalam Persfektif Akidah dan Syariat - Islamul Haq (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
Crime is a problem that is experienced by human beings since years ago, so that it can be stated that where there is a man there is a crime. Crime is an act or behaviour that can destruct the victims and the community in the form of the loss of balance, peace and order. This paper aims to understand and analyse the Islamic faith and sharia approach to the crime. The method used in this paper is a literature study to comprehensively uncover the concept of punishment to the criminals from the religious text. The result of the research showed that aqeedah considers the criminalities as a part of disgrace or humiliation of human. Repentance, taubat, is a way to improve bad behaviours related to crime. The approach of Islamic faith to the criminality focuses on the efforts to look up criminal behaviour. Meanwhile, sharia views criminality as a bad thing and to look it up, there should be punishments, namely: Qishas, Hudud or Takzir. Thus, the sharia approach focuses more on the victims of criminality. Therefore, the approach of Islamic faith and sharia cannot be separated from one another, so the duality between both is very appropriate to prevent and reduce the crime.